2019
DOI: 10.3389/fimmu.2019.01059
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inflammation in Neutrophil-Mediated Skin Diseases

Abstract: Neutrophil-mediated skin diseases, originally named neutrophilic dermatoses (NDs), are a group of conditions due to an altered neutrophil recruitment and activation, characterized by polymorphic cutaneous manifestations with possible internal organ involvement. Although a number of diseases are included in this setting, the two prototypic forms are pyoderma gangrenosum (PG) and Sweet's syndrome (SS) which usually present with skin ulcers and plaque-type lesions, respectively. They have central features signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 89 publications
4
99
0
Order By: Relevance
“…Inadequate negative or positive regulation of innate immune receptors, may lead to signals that stimulate nucleic acid and subsequent protein transcription, which can occur as monogenic genetic disorders, with gain in function (GOF) or loss of function (LOF). These are known as type I interferonopathies or other autoinflammatory diseases [76][77][78][79][80][81].…”
Section: Possible Actions Of Sars-cov-2 On Human Skin and The Resultimentioning
confidence: 99%
“…Inadequate negative or positive regulation of innate immune receptors, may lead to signals that stimulate nucleic acid and subsequent protein transcription, which can occur as monogenic genetic disorders, with gain in function (GOF) or loss of function (LOF). These are known as type I interferonopathies or other autoinflammatory diseases [76][77][78][79][80][81].…”
Section: Possible Actions Of Sars-cov-2 On Human Skin and The Resultimentioning
confidence: 99%
“…CAPS are a group of rare inherited inflammatory disorders associated with dominant mutations in the cryopyrin‐coding gene NLRP3 (nucleotide‐binding domain, leucine‐rich repeat containing gene family, pyrin domain‐containing protein 3) on chromosome 1q44 which is also known as CIAS1, PYPAF1 or NALP3. Currently, more than 90 mutations involving NLRP3 and associated with CAPS phenotypes have been reported 57 …”
Section: Skin Conditions Related To Hypercoagulability That Show Histmentioning
confidence: 99%
“…Still, no triggers have been identified. 24,47,48 The first study to demonstrate IL-8 overexpression in tissue was performed by Oka et al 49 51 performed a study using human skin biopsies of PG which showed that abundant expression of matrix metalloproteinase (MMP) 9, MMP-10, and TNF-α, and lack of epithelial MMP-1 and MMP-26 characterised PG. This marked the first multipatient molecular-level study of PG.…”
Section: Brocqmentioning
confidence: 99%